2012
DOI: 10.1098/rspb.2012.1841
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiological consequences of immune priming

Abstract: Exposure to low doses of pathogens that do not result in the host becoming infectious may 'prime' the immune response and increase protection to subsequent challenge. There is increasing evidence that such immune priming is a widespread and important feature of invertebrate host-pathogen interactions. Immune priming clearly has implications for individual hosts but will also have population-level implications. We present a susceptible-primed-infectious model-in contrast to the classic susceptibleinfectious-rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 42 publications
(51 reference statements)
1
79
1
Order By: Relevance
“…Transgenerational immune priming is predicted to have not only a strong effect on disease prevalence [65,66], but also on the age structure [65] and population dynamics of invertebrates [66]. Our theoretical model shows that, beyond the effect of host lifespan and host dispersal, several other life-history parameters play a key role in the evolution of transgenerational immunity.…”
Section: Discussionmentioning
confidence: 98%
“…Transgenerational immune priming is predicted to have not only a strong effect on disease prevalence [65,66], but also on the age structure [65] and population dynamics of invertebrates [66]. Our theoretical model shows that, beyond the effect of host lifespan and host dispersal, several other life-history parameters play a key role in the evolution of transgenerational immunity.…”
Section: Discussionmentioning
confidence: 98%
“…As well as potentially suffering reduced fecundity, infected hosts suffer through a further death rate (defined here as virulence) a. For analytical ease, we make two notable simplifications to the model of Tidbury et al [18]: we do not include maternal priming and we assume that priming is permanent (the impact of these assumptions is considered in §4).…”
Section: Modelmentioning
confidence: 99%
“…However, as of yet there has been no theoretical study of the evolution of immune priming. Two recent papers have, however, investigated the impact on host population dynamics, finding that immune priming can reduce the prevalence of infection considerably [17,18]. Furthermore, Tidbury et al [18] found that the population dynamics of hosts with primed immunity are more complex than in classic models with acquired immunity, with the potential for bistability between disease-free and endemic states as well as for endemic cycles.…”
Section: Introductionmentioning
confidence: 99%
“…This persistent priming also has broad implications for understanding the epidemiological consequences of priming. For example, Tidbury et al (Tidbury et al, 2012) showed that immune priming may increase the persistence of the pathogen and destabilise host-pathogen dynamics. We suggest that the linked effects of the phenomena reported here -age effects, maternal effects and priming -merit further study as major drivers of disease spread and host-pathogen evolution in this and other systems.…”
Section: Research Articlementioning
confidence: 99%